“And Here We are in the Fairyland” of Children’s Literature: The Case of the French Version of Internatsionalnaya Literatura” (1934) - Evgenia V. Belskaya (Studia Litterarum)
This article focuses on the issue of La Littérature Internationale, a French version of the multilingual Soviet journal Internatsionalnaya Literatura, which embodied one of the declarations of the First Congress of the Soviet writers on the key role of didacticism in the new literature. The second issue of La Littérature Internationale in 1934 contained a selection of works about children by authors from the USSR, France, United States, and Germany. The aim of this article is to analyze this selection of texts and to determine its function in the literary journal for adults. The author shows the connection of the plot schemes in the selection with the preceding folklore and literary tradition (a folk fairytale and literary Christmas tale, Victorian educational novel, romantic heroic novel). The classic storyline of these works allows us to introduce new themes and plots: re-education and correction, the story of working at the factory and at the mine, shown through the eyes of children as well as the resistance to Hitler’s regime in Germany. The conclusion shows that in this issue, the children’s selection forms a socialist realist model of world literature of a kind. Together with the stories for adults, it sets a pattern for the new universal literature whose plot schemes reflect the main trends in the literature of socialist realism and the anti-fascist literature of the 1930s–1940s.